Erland Barlian1* , Didi Supardi2 , Adi Teguh Suprapto3 and Yosef PradiptoErland Barlian1* , Didi Supardi2 , Adi Teguh Suprapto3 and Yosef Pradipto - Erland Barlian, Didi Supardi , Adi Teguh Suprapto, Yosef Pradipto (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Despite high number of Internet users and high growth of Internet utilization for business purpose. Small and Medium Enterprise (SME) firms intention to use Internet and e-commerce are consider low compare to larger companies. It is found that researchers around the world are also found the same fact that adoption e-commerce among SMEs are relatively low. Therefore, we are doing a research of SMEs in Indonesia and their intention for using ecommerce platform. We are using SmartPls 3.0 Program to analyze 62 companies in the event and wedding industry throughout Jakarta and Greater Jakarta Area. Through our works we discover that Entrepreneur in Indonesia SME has greater intention to use e-commerce platform when it is mediated with Technology Orientation using UTAUT (Unified Theory of Acceptance and Use of Technology) model compare to one without mediation of technology orientation towards using e-commerce platform.